(untitled) (Research, Society and Development, 2022)
Renal cell carcinoma is a type of malignant tumor that affects the renal tubules. Its incidence increases every year, and its diagnosis occurs incidentally through the imaging tests. Objective: To review the importance of imaging techniques used in the diagnosis of renal cell carcinoma. Methodology: Integrative review. Results and Discussion: Through the comparative tables elaborated for differentiation of the methods used in the diagnosis of renal cell carcinoma and the selected works, it was observed that the Computed Tomography is considered the method of choice for this diagnosis with its multiplanar reconstructions. Magnetic resonance imaging is the modality of choice in cases of allergy to contrast tomography, and / or the evaluation of the presence of thrombi. Ultrasound is not very efficient in assessing this diagnosis. On the other hand, scintigraphy is also recommended in this diagnosis and should not be adopted in routine practice.